2023
DOI: 10.3390/antibiotics12020292
|View full text |Cite
|
Sign up to set email alerts
|

A European International Multicentre Survey on the Current Practice of Perioperative Antibiotic Prophylaxis for Paediatric Liver Transplantations

Abstract: (1) Background: Postoperative infections are major contributors of morbidity and mortality after paediatric liver transplantation (pLTX). Evidence and recommendations regarding the most effective antimicrobial strategy are lacking. (2) Results: Of 39 pLTX centres, 20 responded. Aminopenicillins plus ß-lactamase inhibitors were used by six (30%) and third generation cephalosporins by three (15%), with the remaining centres reporting heterogenous regimens. Broad-spectrum regimens were the standard in 10 (50%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Current clinical practice differs from the mentioned recommendations. A study on regimes in different pediatric transplant centers found a huge variety: from single shot antibiotic to more than a week, and from narrow spectrum to broad‐spectrum antibiotic drug [21]. Currently, no data on the clinical value of PAP in children after liver transplantation are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current clinical practice differs from the mentioned recommendations. A study on regimes in different pediatric transplant centers found a huge variety: from single shot antibiotic to more than a week, and from narrow spectrum to broad‐spectrum antibiotic drug [21]. Currently, no data on the clinical value of PAP in children after liver transplantation are available.…”
Section: Introductionmentioning
confidence: 99%
“…Time to SSI, median (IQR)19 12(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Abbreviations: IQR, interquartile range; MDR, multidrug resistant; SSI, surgical site infections.…”
mentioning
confidence: 99%